Sosialisasi Faktor Risiko dengan Kejadian Stunting Pada Balita (12-59 bulan) di Kecamatan Kuripan Kabupaten Lombok Barat Tahun 2020 - Sekar Partiwi (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Stunting is a condition of being body short and very short over deficit -2 SD under length median or body height. Stunting is a public health problem since related to increasing number of sickness and death, late for movement development and mentally development hampered. This study was aimed to know the relatinship between risk factor and stunting on under five years old children (12-59 months) Kuripan district of West Lombok Regency in 2020. Type of the study is observational analytic with case control design study by using retrospective approach. There are 82 under five years old children teken as samples that divided into 41 under five yaears old children as case sample (stunting) and other 41 under five years old children as control samples (normal). The variables are stunting, delivery weight, number of family, mother’s body height, father's body height, age when delivery and disease on pregnant record. Data are analyzed by using chi square test (bivariate) and double logistic regression (multivariate). The results of bivariat analysis by using chi square showed there was a significant relationship between delivery weight, number of family, mother’s body height and disease on pregnant record toward stunting. The result of multivariate analysis by using double logistic regression showed that variable mother’s body height is the dominant risk factor toward stunting on under five years old children (12-59 months) after controlling by variables of delivery weight, number of family and disease on pregnant record.